Lithium sulfur battery with high energy density
Patent Information
- Application Number
- CN202180032796.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-29
- Filing Date
- 2021-09-28
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2041-09-28
AI Technical Summary
因为使用现有阴极电解质体系的锂硫电池依赖于生成了具有Li2Sx形式的中间多硫化物的液体反应(阴极电解质型),因此存在着以下问题:硫的高理论放电容量(1,675mAh/g)未被充分利用,相反,由于多硫化物溶出导致电池劣化而使电池寿命迅速下降
[0018] The lithium-sulfur battery with high energy density according to the present invention has the advantage of maximizing the discharge capacity and lifespan performance of the battery even without the use of nitrile solvents, by using a microsolubilized electrolyte (SSE) system (discharge capacity: ~1,600 mAh/gs) instead of the existing cathode electrolyte system (discharge capacity: ~1,200 mAh/gs) and by simultaneously using a cathode carbon material with a high specific surface area, while also utilizing more than 90% of the high theoretical discharge capacity (1,675 mAh/g) of sulfur. Furthermore, the lithium-sulfur battery with high energy density according to the present invention has the advantage of maximizing the discharge capacity and lifespan performance even at 4.0 mAh/cm². 2 The system of electrolyte and positive electrode active materials that can be driven at porosities of 60% or more can maintain an energy density of approximately 400 Wh/kg or 600 Wh/L or more.
Smart Images

Figure CN115485904B_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to Korean Patent Application No. 10-2020-0126558, filed on September 29, 2020, the entire contents of which are incorporated herein by reference.
[0002] This invention relates to a lithium-sulfur battery with high energy density that can utilize more than 90% of the high theoretical discharge capacity of sulfur. More specifically, it relates to a lithium-sulfur battery with high energy density that can utilize more than 90% of the high theoretical discharge capacity (1,675 mAh / g) of sulfur, even without the use of nitrile solvents, by using a sparing solvating electrolyte (SSE) system (discharge capacity: ~1,600 mAh / gS) instead of the existing cathode electrolyte system (discharge capacity: ~1,200 mAh / gS) and by further maximizing performance by simultaneously using a cathode carbon material with a high specific surface area. Background Technology
[0003] As interest in energy storage technologies grows and applications expand from mobile phones, tablets, laptops, and cameras to electric vehicles (EVs) and hybrid electric vehicles (HEVs), research and development of electrochemical devices have increased. Electrochemical devices are among the most closely watched areas, and even within these, the development of rechargeable batteries, such as rechargeable lithium-sulfur batteries, remains a focus. In recent years, the development of these batteries has driven research and development into new electrode and battery designs aimed at improving capacity density and specific energy.
[0004] Among these electrochemical devices, lithium-sulfur batteries (Li-S batteries) have attracted attention as a next-generation secondary battery that can replace lithium-ion batteries due to their high energy density (theoretical capacity). In this type of lithium-sulfur battery, sulfur reduction and lithium metal oxidation occur during discharge, at which point sulfur is converted from the cyclic structure of S8 to lithium polysulfides (LiPS) with a linear structure. A characteristic of this type of lithium-sulfur battery is that it exhibits a phased discharge voltage until the polysulfides are completely reduced to Li2S.
[0005] However, the biggest obstacle to the commercialization of lithium-sulfur batteries is lifespan. Charge / discharge efficiency decreases during charging / discharging, leading to a reduction in battery life. The reasons for this reduced lifespan are varied, including electrolyte side reactions (byproduct deposition due to electrolyte decomposition), lithium metal instability (dendritic growth on the lithium anode causing short circuits), and cathode byproduct deposition (lithium polysulfides dissolving from the cathode), among others.
[0006] In batteries using sulfur compounds as the positive electrode active material and alkali metals such as lithium as the negative electrode active material, lithium polysulfide dissolution and shuttle phenomena occur during charge / discharge. Lithium polysulfides are transported to the negative electrode, thus reducing the capacity of the lithium-sulfur battery. Therefore, lithium-sulfur batteries suffer from significant problems of reduced lifespan and decreased reactivity. Specifically, because polysulfides dissolved from the positive electrode have high solubility in organic electrolytes, they may undesirably migrate to the negative electrode through the electrolyte (PS shuttle). As a result, capacity decreases due to irreversible loss of the positive electrode active material, and battery life is further reduced due to sulfur particle deposition on the lithium metal surface caused by side reactions.
[0007] On the other hand, the behavior of lithium-sulfur batteries can vary significantly depending on the electrolyte. When sulfur from the cathode dissolves into the electrolyte as lithium polysulfides (LiPS), the electrolyte is called a cathode electrolyte; when almost no sulfur dissolves as lithium polysulfides, the electrolyte is called a microsolubilized electrolyte (SSE). This is because lithium-sulfur batteries using existing cathode electrolyte systems rely on the formation of Li2S... x The liquid reaction of intermediate polysulfides (cathode electrolyte type) has the following problems: the high theoretical discharge capacity of sulfur (1,675 mAh / g) is not fully utilized, and instead, the battery life decreases rapidly due to battery degradation caused by polysulfide dissolution.
[0008] Conversely, a microsolvated electrolyte (SSE) system capable of suppressing polysulfide dissolution has recently been developed to utilize over 90% of the theoretical discharge capacity of sulfur; however, this SSE system is almost entirely dependent on nitrile solvents. In this case, there is a fatal drawback in terms of battery life because the lithium anode deteriorates through reactions with the lithium anode and gas is generated inside the lithium-sulfur battery.
[0009] Therefore, various studies have been conducted in this field on lithium-sulfur batteries where sulfur, as the positive electrode active material, does not dissolve into the electrolyte (such as adding LiPS adsorbents to the positive electrode composite material and modifying PE-based separators in related fields). Specifically, even electrolytes where sulfur can undergo a solid-solid reaction with Li₂S, the final discharge product, have been studied, but no meaningful results have been obtained. Therefore, there is a need to develop an innovative battery with high energy density (meaning an energy density of approximately 400 Wh / kg or higher, or 600 Wh / L or higher; to achieve high energy density, even at 4.0 mAh / cm³) that does not degrade the lithium anode or generate gas in the battery, even when using an SSE system that utilizes more than 90% of the theoretical discharge capacity of sulfur. 2 Electrolyte and positive electrode active material systems that can be driven even at porosities above and below 60%. Summary of the Invention
[0010] Technical issues
[0011] Therefore, the object of the present invention is to provide a lithium-sulfur battery with high energy density, which, even without the use of nitrile solvents, can achieve more than 90% of the high theoretical discharge capacity (1,675 mAh / g) of sulfur by using a microsolventized electrolyte (SSE) system (discharge capacity: ~1,600 mAh / gs) instead of the existing cathode electrolyte system (discharge capacity: ~1,200 mAh / gs) and by simultaneously using a cathode carbon material with a high specific surface area.
[0012] Technical solution
[0013] To achieve the aforementioned objective, the present invention provides a lithium-sulfur battery, the lithium-sulfur battery comprising:
[0014] The electrolyte comprises a first solvent containing a fluorinated ether compound, a second solvent containing a glycol diether compound, and a lithium salt; and
[0015] The positive electrode comprises sulfur and carbon materials as active materials.
[0016] The sulfur contained in the positive electrode is utilized at a rate of over 90% of the theoretical discharge capacity.
[0017] Beneficial effects
[0018] The lithium-sulfur battery with high energy density according to the present invention has the advantage of maximizing the discharge capacity and lifespan performance of the battery even without the use of nitrile solvents, by using a microsolubilized electrolyte (SSE) system (discharge capacity: ~1,600 mAh / gs) instead of the existing cathode electrolyte system (discharge capacity: ~1,200 mAh / gs) and by simultaneously using a cathode carbon material with a high specific surface area, while also utilizing more than 90% of the high theoretical discharge capacity (1,675 mAh / g) of sulfur. Furthermore, the lithium-sulfur battery with high energy density according to the present invention has the advantage of maximizing the discharge capacity and lifespan performance even at 4.0 mAh / cm². 2 The system of electrolyte and positive electrode active materials that can be driven at porosities of 60% or more can maintain an energy density of approximately 400 Wh / kg or 600 Wh / L or more. Attached Figure Description
[0019] Figure 1 and Figure 2 The graph shows the discharge capacity and lifespan characteristics of lithium-sulfur batteries manufactured according to embodiments and comparative examples of the present invention. Detailed Implementation
[0020] The invention will be described in more detail below.
[0021] The lithium-sulfur battery according to the present invention comprises:
[0022] The electrolyte comprises a first solvent containing a fluorinated ether compound, a second solvent containing a glycol diether compound, and a lithium salt; and
[0023] The positive electrode comprises sulfur and carbon materials as active materials.
[0024] The sulfur contained in the positive electrode is utilized at a rate of over 90% of the theoretical discharge capacity.
[0025] Recently, a microsolventized electrolyte (SSE) system capable of suppressing polysulfide dissolution has been developed to utilize more than 90% of the theoretical discharge capacity of sulfur. However, since the characteristics of the SSE system depend on nitrile solvents, the lithium anode deteriorates due to the reaction with the lithium anode and gas is generated inside the lithium-sulfur battery, thus failing to solve the problem of shortened battery life.
[0026] Therefore, by including even at 4.0mAh / cm 2 The applicant has developed a lithium-sulfur battery with a high energy density of about 400 Wh / kg or more, or 600 Wh / L or more, by using a stable ether electrolyte solvent instead of a nitrile electrolyte, which also has a fatal impact on the lifespan of the lithium-sulfur battery, in a SSE system where the theoretical discharge capacity can be used even with a sulfur utilization rate of more than 90%, preferably 90% to 100%, more preferably 94% to 100%. On the other hand, "sulfur utilization rate" specifically refers to the ratio of the discharge capacity (mAh) of sulfur element per unit weight (g) included in the positive electrode of the corresponding battery to the theoretical capacity of 1,675 mAh / g (sulfur) per unit weight of sulfur. For example, when the discharge capacity of sulfur element per unit weight included in the positive electrode of the lithium-sulfur battery is 1,600 mAh / g (sulfur), the sulfur utilization rate is 95.5% (1,600 / 1,675).
[0027] Specifically, the applicant has discovered a method to compensate for the problem in the related field that battery performance could not be maximized even when using an SSE system, and then confirmed a synergistic effect between an electrolyte comprising a first solvent containing a fluorinated ether compound, a second solvent containing a glycol diether compound, and a lithium salt, and a positive electrode comprising sulfur and carbon materials as active materials. As a result, the applicant has completed a lithium-sulfur battery with a high energy density of about 400 Wh / kg or more or 600 Wh / L or more, while using sulfur, achieving more than 90% of the theoretical discharge capacity (i.e., an initial discharge capacity of about 1,507 mAh / g or more), preferably 90% to 100%, and more preferably 94% to 100%.
[0028] The lithium-sulfur battery of the present invention will be described in detail below as including A) a first solvent containing a fluorinated ether compound, B) a second solvent containing a diol diether compound, C) a lithium salt, and D) a positive electrode.
[0029] A) First solvent
[0030] The first solvent is an electrolyte solvent containing a fluorinated ether compound. It improves battery life by enhancing coulombic efficiency (CE) through its solubility and solvent decomposition inhibition of polysulfides. More specifically, compared to general organic solvents containing alkanes, the first solvent containing the fluorinated ether compound exhibits excellent solvent structural stability and very high stability due to fluorine substitution. Therefore, when the first solvent is used in the electrolyte of a lithium-sulfur battery, it can significantly improve the stability of the electrolyte, thereby enhancing the battery's lifespan.
[0031] Examples of the fluorinated ether compounds may include at least one hydrofluoroether (HFE type) compound selected from 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), bis(fluoromethyl) ether, 2-fluoroethyl methyl ether, bis(2,2,2-trifluoroethyl) ether, propyl 1,1,2,2-tetrafluoroethyl ether, isopropyl 1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl isobutyl ether, 1,1,2,3,3,3-hexafluoropropyl ethyl ether, 1H,1H,2'H,3H-decafluorodipropyl ether and 1H,1H,2'H-perfluorodipropyl ether.
[0032] B) Second solvent
[0033] The second solvent is an electrolyte solvent containing glycol diether compounds (but without fluorine). The second solvent not only has the lithium-ion conductivity of an electrolyte by dissolving lithium salts, but also smoothly undergoes an electrochemical reaction with lithium by dissolving sulfur, which serves as the positive electrode active material.
[0034] Examples of the diol diether compounds may include, but are not limited to, at least one selected from dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether, wherein dimethoxyethane is preferred.
[0035] C) lithium salts
[0036] The lithium salt is an electrolyte salt used to increase ionic conductivity and can be used without restriction, as long as it is a lithium salt commonly used in the art. Specific examples of the lithium salt may include those selected from LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB. 10 Cl 10 At least one of the following: LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium lower aliphatic carboxylic acids having 4 or fewer carbon atoms, lithium tetraphenylborate, and lithium imide.
[0037] The concentration of the lithium salt can be determined by considering factors such as ionic conductivity, and for example, it can be 0.1 to 2 M, preferably 0.5 to 1 M, and more preferably 0.5 to 0.75 M. When the concentration of the lithium salt is below the above range, it may be difficult to ensure ionic conductivity suitable for battery operation, while when its concentration is above the above range, it will increase the viscosity of the electrolyte, thereby reducing the mobility of lithium ions, or increase the decomposition reaction of the lithium salt itself, thereby reducing the performance of the battery.
[0038] In an electrolyte comprising a first solvent, a second solvent, and a lithium salt, the molar ratio of the lithium salt, the second solvent, and the first solvent can be 1:0.5 to 3:4.1 to 15. Furthermore, in one embodiment of the present invention, as in the lithium-sulfur battery of the present invention, the molar ratio of the lithium salt, the second solvent, and the first solvent in the electrolyte can be 1:2:4 to 13, 1:3:3 to 10, or 1:4:5 to 10, with the first solvent containing a fluorinated ether compound having a higher content than the second solvent containing a glycol diether compound. Thus, when the content of the first solvent containing a fluorinated ether compound is higher than that of the second solvent containing a glycol diether compound, there is the advantage of suppressing polysulfide formation, thereby achieving a battery capacity close to the theoretical capacity of sulfur, and preventing the battery capacity from decreasing with battery use. Therefore, it is preferable, where possible, to set the content of the first solvent containing a fluorinated ether compound to be higher than that of the second solvent containing a glycol diether compound.
[0039] D) positive electrode
[0040] The lithium-sulfur battery according to the present invention includes a positive electrode containing sulfur and carbon materials as active materials, a negative electrode, a separator inserted between the positive electrode and the negative electrode, and the above electrolyte comprising A) a first solvent containing the fluorinated ether compound, B) a second solvent containing a diol diether compound and C) a lithium salt. The positive electrode will be described in detail below.
[0041] The positive electrode in the lithium-sulfur battery according to the present invention includes a positive electrode active material, a binder, a conductive material, etc. The positive electrode active material can be used in conventional lithium-sulfur batteries, and may include, for example, elemental sulfur (S₈), sulfur compounds, or mixtures thereof, specifically Li₂S. n (n≥1), organic sulfur compounds, sulfur-carbon composite materials (C2S) x (n: x = 2.5~50, n≥2), etc. Furthermore, the positive electrode active material may include a sulfur-carbon composite material, because sulfur materials themselves are not conductive, therefore the sulfur materials can be combined with conductive materials and used together.
[0042] The particle size of the sulfur-carbon composite material can be from 1 to 100 μm. When the particle size of the sulfur-carbon composite material is less than 1 μm, the resistance between particles increases, which may cause overvoltage in the lithium-sulfur battery electrode. When the particle size is greater than 100 μm, the surface area per unit weight is reduced, thereby reducing the wetting area with the electrolyte and the reaction sites between lithium ions in the electrode, reducing the amount of electrons transferred relative to the size of the composite material, and delaying the reaction, thus reducing the discharge capacity of the battery.
[0043] The sulfur (S) content relative to the total weight of the positive electrode can be 60% to 80% by weight, preferably 67.5% to 75% by weight. In typical lithium-sulfur batteries, the sulfur content in the positive electrode is approximately 40% to 60% by weight relative to the total weight of the positive electrode. According to the present invention, despite a significantly higher sulfur content, an initial discharge capacity of approximately 1,550 mAh / g or more is observed under the electrolyte conditions of the present invention. When less than 60% by weight of sulfur is used relative to the total weight of the positive electrode, there is a potential problem of reduced battery energy density, while when more than 80% by weight of sulfur is used, there may be problems of decreased electrode conductivity and decreased electrode stability.
[0044] The carbon material (or sulfur carrier material) constituting the sulfur-carbon composite material has porosity; specifically, the carbon material used as the positive electrode active material of this invention has a high specific surface area (3,000 m²). 2 / g or more) and high pore volume (0.7~3cm) 3 Due to its properties of ( / g), it can be driven at high capacity (1,575 to 1,675 mAh / g) in electrolytes.
[0045] Porous carbon materials, for example, can have a thickness of 0.7–3 cm. 3 All carbon materials with a pore volume of / g, specifically, for example, can be selected from materials satisfying 0.7 to 3 cm³. 3 Graphite with a pore volume of / g; graphene; reduced graphene oxide (rGO); carbon black such as Denca black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal cracking black; carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs); carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs); and at least one of activated carbon. Furthermore, its shape can be spherical, rod-shaped, bed-shaped, plate-shaped, tubular, block-shaped, etc.
[0046] Based on 100 parts by weight of the total positive electrode weight, the content of positive electrode active material, including sulfur and carbon materials, can be 80 to 99 parts by weight, preferably 90 to 95 parts by weight. Based on 100 parts by weight of the total positive electrode weight, when the content of positive electrode active material is less than 80 parts by weight, there may be a problem of decreased battery energy density, while when its content exceeds 99 parts by weight, there may be problems of decreased electrode conductivity and decreased electrode stability.
[0047] On the other hand, the positive electrode of the lithium-sulfur battery according to the present invention may further include a binder and a conductive material. Furthermore, in the positive electrode, a matrix solid containing the active material, binder, and conductive material may be located on the current collector.
[0048] The adhesive is a component that facilitates the adhesion of positive electrode active materials, conductive materials, etc., and to current collectors. For example, it may be selected from at least one of polyvinylidene fluoride (PVdF), polyvinylidene fluoride-polyhexafluoropropylene copolymer (PVdF / HFP), polyvinyl acetate, polyvinyl alcohol, polyvinyl ether, polyethylene, polyethylene oxide, alkylated polyethylene oxide, polypropylene, poly(meth)acrylate, poly(meth)acrylate, polytetrafluoroethylene (PTFE), polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polyvinylpyrrolidone, styrene-butadiene rubber, acrylonitrile-butadiene rubber, ethylene propylene diene monomer (EPDM) rubber, sulfonated EPDM rubber, styrene-butene rubber, fluororubber, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, and mixtures thereof, but is not limited thereto.
[0049] Based on 100 parts by weight of the total positive electrode weight, the binder is typically added to 1 to 50 parts by weight, preferably 3 to 15 parts by weight. If the content of the binder is less than 1 part by weight, the adhesion between the positive electrode active material and the current collector may be insufficient. When the content of the binder exceeds 50 parts by weight, the adhesion is improved, but the content of the positive electrode active material is reduced, which may reduce the battery capacity.
[0050] There are no particular limitations on the conductive materials included in the positive electrode, as long as they have excellent conductivity, do not cause side reactions in the internal environment of the battery, and do not cause chemical changes in the corresponding battery. Representative conductive materials can be graphite or conductive carbon. For example, graphite such as natural graphite and artificial graphite can be used alone or in combination of two or more of them; carbon black such as carbon black, acetylene black, Ketjen black, Tenca black, thermal cracking carbon black, channel black, furnace black, lamp black, thermal cracking carbon black, etc.; carbon materials with the crystal structure of graphene or graphite; carbon nanotubes; conductive fibers such as carbon fiber and metal fiber; fluorinated carbon; metal powders such as aluminum powder and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, but are not necessarily limited to these.
[0051] Based on 100 parts by weight of the total positive electrode weight, the conductive material can typically be added from 0.5 to 10 parts by weight, preferably from 0.5 to 5 parts by weight, but may not be included in the positive electrode of the present invention. When the content of the conductive material is too high, exceeding 10 parts by weight, the amount of the positive electrode active material is relatively small, which may degrade the capacity and energy density. There are no significant limitations on the method of including the conductive material in the positive electrode; general methods known in the art can be used, such as coating the positive electrode active material. Furthermore, if necessary, a second conductive coating can be added to the positive electrode active material instead of adding the conductive material as described above.
[0052] Furthermore, in the positive electrode of the present invention, fillers can be selectively added as components to suppress expansion. There are no particular limitations on the fillers, as long as they can suppress electrode expansion without causing chemical changes in the corresponding battery. For example, olefin polymers such as polyethylene and polypropylene; fibrous materials such as glass fiber and carbon fiber; and so on can be used.
[0053] The positive electrode can be manufactured by dispersing and mixing the positive electrode active material, the binder, the conductive material, etc., in a dispersant (solvent) to form a slurry, coating the slurry onto the positive electrode current collector, and then drying and rolling it. The dispersant can be N-methyl-2-pyrrolidone (NMP), dimethylformamide (DMF), dimethyl sulfoxide (DMSO), ethanol, isopropanol, water, and mixtures thereof, but is not necessarily limited to these.
[0054] The positive electrode current collector can be made of platinum (Pt), gold (Au), palladium (Pd), iridium (Ir), silver (Ag), ruthenium (Ru), nickel (Ni), stainless steel (STS), aluminum (Al), molybdenum (Mo), chromium (Cr), carbon (C), titanium (Ti), tungsten (W), in-doped SnO2 (ITO), f-doped SnO2 (FTO) and their alloys, as well as aluminum (Al) or stainless steel with carbon (C), nickel (Ni), titanium (Ti) or silver (Ag) surface treatment, but is not necessarily limited to these. The positive electrode current collector can be in the form of foil, film, sheet, stamped form, porous body, foam, etc.
[0055] The negative electrode can be a lithium-based metal, and may also include a current collector on the lithium-based metal side. The current collector can be used as the negative electrode current collector. There are no particular limitations on the negative electrode current collector, as long as it has high conductivity without causing chemical changes in the battery, and it can be selected from copper, aluminum, stainless steel, zinc, titanium, silver, palladium, nickel, iron, chromium, their alloys, and combinations thereof. Stainless steel can be surface-treated with carbon, nickel, titanium, or silver; alloys can use aluminum-cadmium alloys; in addition, ductile carbon, non-conductive polymers surface-treated with conductive materials, or conductive polymers can be used. Typically, a thin copper sheet is used as the negative electrode current collector.
[0056] Furthermore, the form can take many forms, such as films, sheets, foils, meshes, porous bodies, foams, and nonwoven fabrics with or without micro-uneven surfaces. Additionally, the thickness of the negative electrode current collector ranges from 3 to 50 μm. When the thickness of the negative electrode current collector is less than 3 μm, the current collection efficiency decreases, while when the thickness exceeds 50 μm, the processability deteriorates during battery folding and assembly.
[0057] The lithium metal can be lithium or a lithium alloy. In this case, the lithium alloy includes elements capable of alloying with lithium, specifically, it can be an alloy of lithium with at least one selected from Si, Sn, C, Pt, Ir, Ni, Cu, Ti, Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Sb, Pb, In, Zn, Ba, Ra, Ge, and Al.
[0058] The lithium metal can be in the form of sheets or foils. In some cases, lithium or lithium alloys can be deposited or coated on the current collector by dry deposition or coating, or granular metals and alloys can be deposited or coated by wet deposition or coating.
[0059] A conventional diaphragm can be inserted between the positive and negative electrodes. The diaphragm is a physical diaphragm that functions to physically separate the electrodes and can be used without particular restrictions, as long as the diaphragm is used as a conventional diaphragm. Specifically, a diaphragm with low resistance to the movement of electrolyte ions and excellent electrolyte moisture retention is preferred.
[0060] Furthermore, the separator is capable of transporting lithium ions between the positive and negative electrodes while simultaneously separating or isolating them from each other. Such a separator can be made of a porous, non-conductive, or insulating material. The separator can also be a standalone component, such as a membrane, or it can be a coating added to the positive and / or negative electrodes.
[0061] Examples of polyolefin porous membranes that can be used as diaphragms can include membranes formed from individual polyolefin polymers, such as polyethylene (e.g., high-density polyethylene, linear low-density polyethylene, low-density polyethylene, and ultra-high molecular weight polyethylene), polypropylene, polybutene, polypentene, etc., or mixtures thereof. Examples of nonwoven fabrics that can be used as diaphragms can be nonwoven fabrics formed from individual or mixtures of polymers such as polyphenylene ether, polyimide, polyamide, polycarbonate, polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polyphenylene sulfide, polyacetal, polyethersulfone, polyetheretherketone, polyester, etc., which are woven fabrics forming porous cloths and include spunbond or meltblown forms composed of long fiber configurations.
[0062] There is no particular limitation on the thickness of the separator, but it is preferably in the range of 1 to 100 μm, more preferably in the range of 5 to 50 μm. When the thickness of the separator is less than 1 μm, it may not be able to maintain mechanical properties, while when the thickness is greater than 100 μm, the separator will act as a resistive layer, thereby degrading the performance of the battery. There is no particular limitation on the pore size and porosity of the separator, but it is preferred that the pore size is 0.1 to 50 μm and the porosity is 10% to 95%. When the pore size of the separator is less than 0.1 μm or the porosity is less than 10%, the separator acts as a resistive layer, while when the pore size of the separator is greater than 50 μm or the porosity is greater than 95%, it may not be able to maintain mechanical properties.
[0063] Thus, the lithium-sulfur battery of the present invention, comprising the electrolyte, positive electrode, negative electrode and separator, can be manufactured by placing the positive and negative electrodes opposite each other, inserting a separator between them, and then injecting an electrolyte.
[0064] On the other hand, the lithium-sulfur battery according to the present invention can be used as a battery cell for use as a power source for small devices, and is particularly suitable as a unit cell for use as a power source for battery modules for medium and large devices. In this respect, the present invention also provides a battery module comprising two or more lithium-sulfur batteries electrically connected to each other (in series or in parallel). Of course, the number of lithium-sulfur batteries included in the battery module can be adjusted differently depending on the purpose and capacity of the battery module. In addition, the present invention provides a battery pack electrically connected to the battery module according to conventional techniques in the art. The battery module and the battery pack can be used as a power source for at least one medium and large device: power tools; electric vehicles, such as electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs); electric trucks; electric commercial vehicles; or energy storage systems, but are not necessarily limited thereto.
[0065] Preferred implementation scheme
[0066] Preferred embodiments will be provided below to aid in understanding the invention. However, the following embodiments are merely illustrative of the invention, and those skilled in the art will readily recognize that various changes and modifications can be made within the scope and concept of the invention, and these changes and modifications are naturally within the scope of the claims.
[0067] [Example 1] Manufacturing of lithium-sulfur batteries
[0068] Preparation of electrolytes
[0069] First, LiTFSI (concentration: 0.65M), dimethoxyethane (second solvent), and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE, first solvent) were mixed at room temperature in a molar ratio of 1:2:9 to prepare an electrolyte for lithium-sulfur batteries.
[0070] Preparation of positive electrode
[0071] 90 parts by weight of a sulfur-carbon composite material (S:C weight ratio = 75:25) was used as the positive electrode active material (the sulfur content alone was set at 67.5% by weight relative to the total weight of the positive electrode, and the carbon material used had a pore volume of 1.8 cm³). 3 A positive electrode slurry composition was prepared by mixing 5 parts by weight of activated carbon ( / g), 5 parts by weight of Denca Black as a conductive material, and 5 parts by weight of styrene-butadiene rubber / carboxymethyl cellulose (SBR:CMC = 7:3) as a binder. The prepared slurry composition was then coated onto a current collector (Al foil), dried at 50°C for 12 hours, and pressed using a roller press to form the positive electrode (at which point the loading was 3.5 mAh / cm²). 2 (The battery porosity is 65%).
[0072] Manufacturing of lithium-sulfur batteries
[0073] A prepared positive electrode and a 150 μm thick lithium metal negative electrode are placed opposite each other, with a polyethylene (PE) separator inserted between them. Then, the prepared electrolyte is injected to manufacture a coin cell type lithium-sulfur battery. Alternatively, in battery manufacturing, the positive electrode is stamped into a Φ14 circular electrode and used, the polyethylene separator is stamped into a Φ19 shape and used, and the lithium metal is stamped into a Φ16 shape and used. Furthermore, the battery is manufactured using a micro-solvated electrolyte (SSE) system.
[0074] [Comparative Example 1] Manufacturing of lithium-sulfur batteries
[0075] The lithium-sulfur battery was manufactured in the same manner as in Example 1, except that dimethoxyethane was replaced with acetonitrile as one of the electrolyte solvents.
[0076] [Comparative Example 2] Manufacturing of lithium-sulfur batteries
[0077] Except for changing the mixing ratio of LiTFSI, dimethoxyethane (second solvent) and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE, first solvent) to a molar ratio of 1:0.8:4, and using a sulfur-carbon composite material as the positive electrode active material but changing the S:C weight ratio of the sulfur-carbon composite material to 46:64, so that the content of sulfur alone is 41% by weight based on the total weight of the positive electrode, the lithium-sulfur battery was manufactured in the same manner as in Example 1.
[0078] [Comparative Example 3] Manufacturing of lithium-sulfur batteries
[0079] The lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the mixing ratio of LiTFSI, dimethoxyethane (second solvent) and 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE, first solvent) was changed to a 1:1:4 molar ratio.
[0080] [Experimental Example 1] Evaluation of the discharge capacity and lifespan characteristics of lithium-sulfur batteries
[0081] The lithium-sulfur batteries manufactured in Example 1 and Comparative Examples 1 to 3 were charged and discharged for three cycles at 0.1C, and then the discharge capacity and life characteristics of the batteries were evaluated. The voltage range used was 1.0 to 3.0V (i.e., discharging to 1.0V and charging to 3.0V), and the evaluation temperatures were set to 25°C and 35°C, respectively (however, Comparative Example 1 was even evaluated at 45°C).
[0082] Figure 1 and Figure 2 This is a graph illustrating the discharge capacity and lifetime characteristics of lithium-sulfur batteries manufactured according to embodiments and comparative examples of the present invention, wherein... Figure 1 a and Figure 2 a corresponds to Example 1. Figure 1 b、 Figure 2 b and Figure 2 c corresponds to Comparative Example 1. First, the reference evaluation temperature was set to 25°C. Figure 1 This study confirmed that, compared to the lithium-sulfur battery of Comparative Example 1, which included nitrile solvents in the electrolyte, the lithium-sulfur battery of Example 1, which used only ether solvents and excluded nitrile solvents in the electrolyte, exhibited superior initial discharge capacity and lifetime characteristics. Specifically, it was confirmed that in the lithium-sulfur battery of Example 1, the initial discharge capacity was close to the theoretical capacity of sulfur, 1,675 mAh / g, and the initial discharge capacity value was at a level not yet exhibited by typical lithium-sulfur batteries using the SSE electrolyte system.
[0083] In addition, such as Figure 2 As shown, even when the evaluation temperature is set to 35°C, similar results are still observed. In the case of Comparative Example 1, where the evaluation temperature is set to 45°C, the lifetime characteristics are improved to some extent compared to evaluations at 25°C and 35°C, but still show significantly lower lifetime characteristics compared to the level of Example 1.
[0084] On the other hand, using the same electrolyte configuration as in Example 1, but with a relatively small amount of the first solvent (including the fluorinated ether compound), and even in Comparative Example 2 where the sulfur content in the positive electrode was lower than that of Example 1, very poor results were observed compared to the initial discharge capacity and lifetime characteristics of Example 1. In Comparative Example 3, where only the amount of the first solvent (including the fluorinated ether compound) was reduced, the results were far inferior to the initial discharge capacity and lifetime characteristics of Example 1.
[0085] The result shows that, in the case of lithium-sulfur batteries using the SSE electrolyte system, without the presence of nitrile solvents in the electrolyte, the performance of the battery can be maximized simply by increasing the mixing ratio of fluorinated ether solvents in the electrolyte to the level of the present invention and increasing the sulfur content ratio in the positive electrode to the level of the present invention.
Claims
1. A lithium-sulfur battery, the lithium-sulfur battery comprising: The electrolyte comprises a first solvent containing only a fluorinated ether compound, a second solvent containing only a glycol diether compound, and a lithium salt; and The positive electrode comprises sulfur and carbon materials as active materials. The sulfur in the positive electrode is utilized at a rate exceeding 90% of the theoretical discharge capacity. The concentration of the lithium salt is 0.1 to 2 M, and the molar ratio of the second solvent to the first solvent is 2:9 to 15. The sulfur content is 67.5% to 75% by weight relative to the total weight of the positive electrode.
2. The lithium-sulfur battery according to claim 1, wherein the fluorinated ether compound comprises at least one hydrofluoroether compound selected from 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether (TTE), bis(fluoromethyl) ether, 2-fluoroethyl methyl ether, bis(2,2,2-trifluoroethyl) ether, propyl 1,1,2,2-tetrafluoroethyl ether, isopropyl 1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl isobutyl ether, 1,1,2,3,3,3-hexafluoropropyl ethyl ether, 1H,1H,2'H,3H-decafluorodipropyl ether and 1H,1H,2'H-perfluorodipropyl ether.
3. The lithium-sulfur battery according to claim 1, wherein the diol diether compound comprises at least one selected from dimethoxyethane, diethoxyethane, methoxyethoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol monomethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.
4. The lithium-sulfur battery according to claim 1, wherein the lithium salt comprises a variety selected from LiCl, LiBr, LiI, LiClO4, LiBF4, and LiB. 10 Cl 10 At least one of the following: LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium lower aliphatic carboxylic acids having 4 or fewer carbon atoms, lithium tetraphenylborate, and lithium imide.
5. The lithium-sulfur battery according to claim 1, wherein the electrolyte does not include nitrile solvents.
6. The lithium-sulfur battery according to claim 1, wherein the pore volume of the carbon material is 0.7 cm³. 3 / g to 3 cm 3 / g.
7. The lithium-sulfur battery according to claim 1, wherein the positive electrode active material included in the positive electrode comprises a sulfur-carbon composite material.
8. The lithium-sulfur battery according to claim 1, wherein the utilization rate of sulfur included in the positive electrode is 94% to 100% of the theoretical discharge capacity.
9. The lithium-sulfur battery according to claim 1, wherein the energy density of the lithium-sulfur battery is 400 Wh / kg or more or 600 Wh / L or more.
Citation Information
Patent Citations
Method for measuring the light intensity of continuous rotation of a polarizer
KR1020200126558A
Lithium-sulfur battery
CN105529464A
Ether electrolyte as well as preparation method and application thereof
CN111224166A
Porous carbon material and method for producing the same, complex and method for producing the same, and positive electrode material for lithium sulfur batteries
JP2018039685A
Electrolyte for lithium secondary battery and lithium secondary battery comprising the same
KR1020180057437A